Salt appetite and addiction: unholy twins? - Ritz, Eberhard (Nephrology, dialysis, transplantation, 2012)
Many behavioural patterns are dependent on neural mechanisms that are of high survival value. Liedtke et al. [ 1 ] ( http://www.pnas.org/content/108/30/12509.lo
Advance access publication 3 May 2012
Gesehen am 29.06.2018